Hanna, S. (2016). Bourdieu in translation studies: The socio-cultural dynamics of Shakespeare translation in Egypt. New York, NY: Routledge. 231p. - Lisheng, Liu (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
/